The Assessment of the Impacts of Carbon Taxation on Chinese Transport and Energy Sectors Based on a Computable General Equilibrium Model - Fu, Miao; Wang, Ling; Xu, Taozi (Asian Journal of Economic Modelling, 2019)
To simulate the effects of carbon taxation on Chinese economy, especially on transport and energy sectors, a computable general equilibrium model was constructed and calibrated with Chinese social accounting matrix and other statistical data. Based on calculated sectoral carbon emissions, a commonly used carbon tax rate of 20 Euros per tonne CO2-eq was converted into a carbon tax rate of 9.94% (tax / energy expenditure) for the transport sector, 1.72% for the energy sector and 9.42% for other sector. The simulation results show that the implementation of these sectoral carbon tax rates will cause a total carbon emission reduction of 40271.6 KT CO2-eqs and an increase of government revenue by 7.17%. However, the carbon tax will also induce approximately a 1.3% loss for the transport sector, a 3% loss for the energy sector and a 0.9% loss for other sectors. Incomes of firms and households will decrease by 4.05% and 0.14%, respectively. It is found that in the transport sector, labour will replace capital due to the increase in energy prices caused by the carbon taxation. The high loss in the energy sector and its subsequence suggest that the energy sector should be exempted from the carbon tax.